(untitled) (Journal of Asian Development Studies, 2019)
Sleep is an important activity which plays a vital role in the physiological and psychological health of the individuals. Lack of sleep is associated with different health problems such as hypersensitivity, diabetes, obesity, attention, concentration and memory problems. Majority students do not give importance to their sleep and mostly remain awake for whole night or late night. Present study was designed to explore the relationship of sleep with the academic achievement of students. The sample (n=120) of the study was consist of male and female college students. The age range of the participants was 16-18 years. Information about the sleep pattern of the participants was taken through a self-report sleep pattern inventory and their academic achievement was determined from their mark sheets. On the basis of the earned grades they were divided into two groups’ i.e. high academic achievers and low academic achievers and their scores on the sleep pattern inventory were analyzed. Measure of mean differences or t-tests were used to compare the sleep pattern of the high and low academic achievers. Results have shown significant differences in the sleep pattern of the high and low academic achiever participants. High achievers were found to have more adequate sleep pattern (sleep of 6-8 hours per night) as compared to low academic achievers who had sleep duration of less than 4 hours. Findings of the present study indicated that awareness must be given to students for maintaining an adequate sleep pattern through organized study schedule for better achievement.